2013
DOI: 10.1371/journal.pone.0070192
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-29c Suppresses Lung Cancer Cell Adhesion to Extracellular Matrix and Metastasis by Targeting Integrin β1 and Matrix Metalloproteinase2 (MMP2)

Abstract: Our pilot study using miRNA arrays found that miRNA-29c (miR-29c) is differentially expressed in the paired low-metastatic lung cancer cell line 95C compared to the high-metastatic lung cancer cell line 95D. Bioinformatics analysis shows that integrin β1 and matrix metalloproteinase 2 (MMP2) could be important target genes of miR-29c. Therefore, we hypothesized that miR-29c suppresses lung cancer cell adhesion to extracellular matrix (ECM) and metastasis by targeting integrin β1 and MMP2. The gain-of-function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 36 publications
(40 reference statements)
1
99
0
Order By: Relevance
“…MiR-29 family has been observed to be aberrently expressed in different types of cancer and be involved in biological functions including cell proliferation, cell cycle, senescence, differentiation, apoptosis and metastasis [19]. As for lung cancer, growing evidence indicates that miR-29 family functions as tumor suppressor and most studies focus on the biology of miR29b [8,[20][21][22][23]. However, despite the high similarity of miR-29a/b/c mature sequence, studies have revealed that different isoforms of miR-29 family may exert distinct functions [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiR-29 family has been observed to be aberrently expressed in different types of cancer and be involved in biological functions including cell proliferation, cell cycle, senescence, differentiation, apoptosis and metastasis [19]. As for lung cancer, growing evidence indicates that miR-29 family functions as tumor suppressor and most studies focus on the biology of miR29b [8,[20][21][22][23]. However, despite the high similarity of miR-29a/b/c mature sequence, studies have revealed that different isoforms of miR-29 family may exert distinct functions [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the high similarity of miR-29a/b/c mature sequence, studies have revealed that different isoforms of miR-29 family may exert distinct functions [24,25]. Concerning the tumor suppressive role of miR-29c in lung cancer, it has been demonstrated to revert aberrant methylation by targeting DNA methyltransferases 3A and 3B and inhibit metastasis by targeting integrin beta1 and matrix metalloproteinase 2 [20,22]. As introduced above, the biological function of miRNA depends on cell types and LAD is a distinct subtype from other histological types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we first measured the expression levels of a panel of miRNAs which have been shown to play important roles in certain cancer types including NSCLC [36][37][38][39][40][41]. Among these miRNAs, miR-29c-3p and miR-497-5p were up-regulated but miR-17-5p was down-regulated in A549-ER cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that miR-29c is downregulated in liver cancer and may affect the apoptosis, tumorigenesis, and prognosis of tumor cells (46). Previous studies have revealed that the overexpression of miR-29c inhibits cancer cell proliferation and metastasis, as well as inducing cell cycle arrest (47,48). Wip1 was also revealed to be significantly upregulated in hepatocellular carcinoma and may contribute to the development of this cancer (49).…”
Section: Wip1 In Liver Cancermentioning
confidence: 98%